A diagenetic study of intrabasaltic siliciclastics sandstones from the Rosebank field. (December 2018) - Sætre, C.; Hellevang, H.; Dennehy, C.; Dypvik, H.; Clark, S.
Abstract: The Rosebank field contains producible hydrocarbons from Paleocene-Eocene intrabasaltic fluvial and shallow marine siliciclastic sandstone reservoirs. Despite close proximity to volcanic lithologies the siliciclastic sandstones display very good reservoirs properties with permeability in the Darcy range and porosity values ranging from 19 to 23%. Preservation of high quality reservoir properties is the result of low quantities of volcanic minerals in the siliciclastic sandstones and limited element diffusion (e.g. Fe and Mg) from adjacent basalts into siliciclastic reservoir sandstones. The low content of volcanic derived detritus is most likely a result of the main sediment source being situated outside the volcanic terrain. The effect is that formation of clay minerals (smectites and or chlorites) reducing permeability and porosity is low. In contrast to the siliciclastic sandstones, the pore space of the volcaniclastics is occupied by authigenic clays (chlorite/smectite) and carbonates (calcite and Mg-calcite) resulting in poor reservoir quality. This paper demonstrates that high quality reservoirs can be found in intrabasaltic siliciclastic reservoirs. In-depth analyses of core samples show that authigenic phases formed during progressive burial with temperatures up to ∼120 °C. The suite of diagenetic phases in siliciclastic sandstones between wells and the different Colsay units vary and are interpreted to result from differences in pore water chemistry and/or detrital mineralogy. Laumontite was formed as a late stage authigenic mineral restricted to cored Colsay 1 and 3 units in well 213/26-1z and has not been observed in the neighbouring 213/27-2 core, which may be explained by differences in pore water pH or CO2 partial pressure. The occurrence of laumontite is often associated with poor reservoir quality, but due to the patchy distribution of this mineral in the Rosebank reservoir sands it appears not to have affected reservoir quality. Highlights: High quality intrabasaltic reservoir sandstones at the Rosebank field. Adjacent mafic lithologies has little to no influence on reservoir quality. Diagenetic phases reflect increasing burial temperature up to ∼120 °C. Presence of laumontite do not affect reservoir quality due to patchy occurrence.